Implementation of Discovery Learning Learning Strategies in View of Prior Knowledge on Mathematics Learning Outcomes of Junior High School Students - Titik Puji Lestari; Nining Setyaningsih (STKIP Singkawang, 2023)
The purposes of study to describe and analyze: (1) the effect of Discovery Learning strategy of Numbered Heads Together (NHT) and Teams Games Tournament (TGT) direct learning in mathematics learning outcomes, (2) the effectsof prior knowledge direct learning in mathematics learning outcomes, (3) interaction Discovery Learning strategy of Numbered Heads Together (NHT) and Teams Games Tournament (TGT) in terms of prior knowledge direct learning in mathematics learning outcomes. The research was conducted students of VII Grade of SMP N 4 Mojosongo, Boyolali with the population all students of VII a number of 144 students, 2 classes were taken as samples, each consisting of 24 students. Type of the research is experiment with quasi experimental design. Methods of data collection use documentation and test. Data analyzed by analysis of variance with two different cell lines. The results of data analysis with a significance level of 5% was obtained: (1) there is effect Discovery Learning strategy of Numbered Heads Together (NHT) and Teams Games Tournament (TGT) direct learning in mathematics learning outcomes, (2) there is effects prior knowledge direct learning in mathematics learning outcomes, (3) there is no interaction Discovery Learning strategy of Numbered Heads Together (NHT) and Teams Games Tournament (TGT) in terms of prior knowledge direct learning in mathematics learning outcomes